2015
DOI: 10.2320/matertrans.m2014454
|View full text |Cite
|
Sign up to set email alerts
|

Martensitic Transformation and Superelastic Properties of Ti-Nb Base Alloys

Abstract: Ti-Nb base alloys have been proposed as prospective candidates for Ni-free biomedical superelastic alloys due to their excellent mechanical properties with good biocompatibility, and many kinds of Ti-Nb base alloys exhibiting shape memory effect or superelasticity have been developed up to now. However, typical Ti-Nb base superelastic alloys show a small recovery strain which is less than one third of the recovery strain of practical Ti-Ni superelastic alloys. Over the last decade there have been extensive eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(39 citation statements)
references
References 98 publications
2
28
0
2
Order By: Relevance
“…It has been reported that non-linear elastic behaviour are due to the formation of nano-domain lattice distortion induced by interstitial oxygen atoms. 10,11) The • 0.2 in TN0.13O and TN 0.24O is related to the first yield stress, which corresponds to the stress for SIMT and is affected by the M s temperature. Oxygen reduces the M s temperature and thereby increases…”
Section: Microstructure and Phase Constitutionmentioning
confidence: 99%
“…It has been reported that non-linear elastic behaviour are due to the formation of nano-domain lattice distortion induced by interstitial oxygen atoms. 10,11) The • 0.2 in TN0.13O and TN 0.24O is related to the first yield stress, which corresponds to the stress for SIMT and is affected by the M s temperature. Oxygen reduces the M s temperature and thereby increases…”
Section: Microstructure and Phase Constitutionmentioning
confidence: 99%
“…One characteristic of these materials is the martensitic transformation from body centered cubic (bcc)-β to orthorhombic-αʺ martensite upon quenching or deformation, which strongly depends on the content of β-stabilizing elements such as Mo, Nb, and Ta [4][5][6][7]. αʺ martensite has been reported to play a key role in several mechanical properties of β-Ti alloys [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, there has been significant progress not only in understanding the martensitic transformation behavior of Ti-based alloys but also in developing novel biocompatible shape memory alloys [1][2][3]. In binary Ti-Nb alloys, superelasticity has been reported to occur when the Ni content is in the range of 26-27 at.% [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been concluded that the small recovery strain is mainly due to the intrinsic small transformation strain of the b-a 00 transformation. [3,5]. Another drawback of Ti-Nb alloys to be mentioned is low critical stress for slip.…”
Section: Introductionmentioning
confidence: 99%